Mengukur Pengalaman Pengguna Aplikasi MochiMochi Menggunakan User Experience Questionnaire - Juliansyah, Rizki; Al Amin, Muhammad; Wicaksana, Arya Dimas; Anwar, Setiady Ibrahim; Lestari, Humannisa Rubina (Innovative: Journal Of Social Science Research, 2025)
This study aims to evaluate the UI (User Interface) and UX (User Experience) of the MochiMochi language learning application using the User Experience Questionnaire (UEQ) as the evaluation tool. A total of 90 users participated in this study and provided responses across six UX dimensions: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. The results showed that all dimensions received positive ratings, with the highest average score found in the Efficiency dimension. These findings indicate that the application's UI is appealing and its UX is generally efficient. However, improvements are needed in the aspect of novelty to further enhance overall user satisfaction and interaction.